Comprehensive meteorological factors analysis and lag correlation study for cyanobacterial blooms in shallow plateau lake - Quan Wang; Tao Wang; Shengping Zhao; Kun Yang; Xinyu Wen; Minhui Zhao; Fen Luo; Baoli Jiang; Yang Jin; Baoying Zhang (Ecological Indicators, 2023)
Cyanobacterial blooms (CBs) are a growing concern for shallow plateau lakes, and numerous studies have investigated the relationship between CBs and meteorological factors. However, these studies have typically lacked comprehensive analyses and neglected the impact of lag effects. This study employed Landsat satellite imagery to extract CBs information from Xingyun Lake from 1990 to 2019 and conducted a lag correlation analysis between meteorological factors ranging from 1 to 30 days with a 1-day step and CBs. The result show that the Sunshine Duration displayed a negative correlation with CBs at an 8-day lag, but when Sunshine Duration was <6 h, it exhibited a positive relationship with CBs at a 1-day lag. And daytime precipitation had a more substantial positive link with CBs than nighttime precipitation at a lag of 13 days. The aforementioned conclusions deepen our comprehension of the meteorological forces that drive cyanobacterial blooms in plateau lakes. Moreover, the maximum and minimum wind velocities were negatively and positively associated with CBs with lags of 20 and 29 days, respectively. In addition, relative humidity and atmospheric pressure were positively associated with cyanobacterial blooms 13–19 days and 3 days after their onset, respectively. The relationship between air temperature and cyanobacterial blooms in Xingyun Lake was weak. Our research emphasizes the significance of incorporating delayed effects and refined meteorological factors for accurate cyanobacterial bloom forecasting.